Determination of non-freezing water in different nonfouling materials by differential scanning calorimetry. Issue 8 (24th May 2022) - Ma, Guanglong; Ji, Fangqin; Lin, Weifeng; Chen, Shengfu
Abstract: Nonfouling materials have attracted increasing interest for their excellent biocompatibility and low immunogenicity. Strong hydration is believed to be the key reason for their resisting capability to nonspecific protein adsorption. However, little attention has been paid to quantifying their strong water binding capacity. In this study, we synthesized four zwitterionic polymers, including poly(sulfobetaine methacrylate) (pSBMA), poly(carboxybetaine methacrylate) (pCBMA), poly(carboxybetaine acrylamide) (pCBAA) and poly(2-methacryloyloxyethyl phosphorylcholine) (pMPC), and compared non-freezing water of these zwitterionic polymers with typical antifouling polymer poly(ethylene glycol) (PEG) using differential scanning calorimetry (DSC). Non-freezing water of their monomers was also investigated. The non-freezing water of the polymers (per unit) is pMPC (10.7 ± 1.4) ≈ pCBAA (10.8 ± 1.5) > pCBMA (9.0 ± 0.6) > pSBMA (6.6 ± 0.4) > PEG20000 (0.60 ± 0.04). Similar trend is observed for their monomers. For all studied zwitterionic materials, they showed higher binding capacity than PEG. We attribute the stronger hydration of zwitterionic polymers to their strong electrostatic interactions. GRAPHICAL ABSTRACT: UF0001